Double-layer gel granular sludge as well as preparation method and application thereof
Double-layer gel granular sludge was prepared by gel cross-linking method, and core-shell structure and cross-linking reaction technology were used to solve the problems of long culture cycle and easy structure disintegration in aerobic granular sludge technology, achieving efficient synchronous nitration denitrification and high stability.
Patent Information
- Application Number
- CN202411855622.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
AI Technical Summary
In actual application, the existing aerobic granular sludge technology has problems such as long culture cycle, easy particle structure disintegration, and small particle size, which limits its rapid promotion in large-scale applications.
Double-layer gel granular sludge was prepared by gel cross-linking method, using a core-shell structure. The core layer includes denitrified sludge and the shell layer includes nitrified sludge. The cross-linking density and strength of the shell are improved through the third cross-linking reaction, and a dissolved oxygen concentration gradient of the core layer anaerobic and aerobic shell layer is constructed.
The high stability of double-layer gel granular sludge and the effective synchronous nitration and denitrification and denitrification process are achieved, which shortens the preparation time and overcomes the problems of long culture cycles and easy structure disintegration in traditional technologies.
Smart Images

Figure CN119661041A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of microbial immobilization and biological denitrification treatment, and in particular to a double-layer gel granular sludge and a preparation method and application thereof. Background Art
[0002] The discharge of nitrogen-containing wastewater directly leads to eutrophication of water bodies, seriously threatening the balance of ecosystems and human health, and has become one of the major challenges in global environmental governance. Traditional sewage treatment technology usually uses a step-by-step nitrification-denitrification process to remove nitrogen from water. However, this method has a series of technical bottlenecks, including complex treatment processes, long processes, high infrastructure and operating costs, and high energy consumption. In addition, with increasingly stringent environmental regulations, traditional sewage treatment technologies are difficult to meet the increasingly stringent nitrogen emission standards, so there is an urgent need to develop new and efficient biological denitrification technologies.
[0003] In this context, simultaneous nitrification and denitrification (SND) technology has gradually attracted attention as an emerging wastewater denitrification technology. The key to SND technology is to simplify the process flow, reduce energy consumption and operating costs by simultaneously performing nitrification and denitrification processes in the same reactor. However, to achieve a stable and effective SND process, it is necessary to establish a stable dissolved oxygen concentration gradient in the microbial growth environment to ensure that nitrification in the outer layer and denitrification in the inner layer occur simultaneously.
[0004] At present, aerobic granular sludge technology is considered to be one of the effective ways to achieve SND. This technology forms an internal and external oxygen transfer barrier through the dense structure of granular sludge, so that the outer layer of the granules is in an aerobic state, while the inside forms an oxygen-deficient or anaerobic environment. It has the advantages of low cost, low energy consumption, and high efficiency. However, in practical applications, aerobic granular sludge still has problems such as long culture cycle (culture cycle is measured in years), easy disintegration of granular structure, and small particle size, which limits its rapid promotion in large-scale applications.
[0005] To overcome the above problems, microbial immobilization technology, especially gel cross-linking method, provides a new technical approach because it can quickly fix microorganisms and form a stable structure. Through this technology, gel granular sludge with a multi-layer structure can be prepared in a relatively short time (preparation cycle is measured in days), effectively controlling the particle size of the granular sludge, enhancing its stability, retaining specific microbial populations and maintaining biological activity, and has great application potential in biological denitrification technology. However, in existing research, the preparation process of double-layer gel granular sludge is not yet mature, especially in how to form a stable double-layer structure and ensure the synergistic effect of inner and outer layer microorganisms, there are still technical challenges. Summary of the invention
[0006] The invention provides a double-layer gel granular sludge and a preparation method and application thereof. The double-layer gel granular sludge prepared by the invention has high stability.
[0007] The present invention provides a method for preparing double-layer gel granular sludge, comprising the following steps:
[0008] (1) mixing a first embedding agent solution with denitrification sludge, and then mixing the obtained core layer embedding material with a first cross-linking agent solution to perform a first cross-linking reaction to obtain core layer gel granular sludge;
[0009] (2) mixing the second embedding agent solution with the nitrified sludge to obtain a shell embedding material;
[0010] (3) coating the core layer gel particle sludge with the shell layer embedding material, and then freezing the obtained coating to obtain double-layer frozen particles;
[0011] (4) mixing the double-layer frozen particles with a second cross-linking agent solution to perform a second cross-linking reaction, and then immersing the particles obtained by the second cross-linking reaction in a third cross-linking agent solution to perform a third cross-linking reaction to obtain the double-layer gel particle sludge;
[0012] There is no order of precedence for step (1) and step (2).
[0013] Preferably, the first embedding agent solution and the second embedding agent solution independently comprise 8-12% polyvinyl alcohol, 0.8-2% sodium alginate and the balance water, calculated by mass fraction.
[0014] Preferably, the mass ratio of the first embedding agent solution to the denitrification sludge is 1 to 3:1;
[0015] The mass ratio of the second embedding agent solution to the nitrified sludge is 1 to 3:1.
[0016] Preferably, the method for preparing the first cross-linking agent solution comprises the following steps:
[0017] Adjust the pH value of the saturated boric acid solution containing calcium chloride to 5.7-6.3 with alkali solution;
[0018] The mass content of calcium chloride in the saturated boric acid solution containing calcium chloride is 1-4%.
[0019] Preferably, the temperature of the first cross-linking reaction is 4 to 30° C., and the time is 6 to 24 hours.
[0020] Preferably, after the first cross-linking reaction, the method further includes: performing solid-liquid separation on the obtained first cross-linking reaction product, then washing the obtained solid, and then immersing the washed solid in a first cross-linking agent solution to obtain a mixture; performing solid-liquid separation on the mixture, removing moisture from the surface of the obtained wet solid, and obtaining the core layer gel granular sludge.
[0021] Preferably, the second cross-linking agent is a saturated boric acid solution containing calcium chloride; the mass content of calcium chloride in the saturated boric acid solution containing calcium chloride is 1 to 4%;
[0022] The second cross-linking reaction time is 1 to 3 hours.
[0023] Preferably, the third cross-linking agent solution includes one of a sodium sulfate solution, a potassium dihydrogen phosphate solution and a sodium nitrate solution; the concentration of the third cross-linking agent solution is 0.5 to 3 M; and the time of the third cross-linking reaction is 1 to 3 hours.
[0024] The present invention also provides a double-layer gel granular sludge prepared by the preparation method described in the above technical scheme, which has a core-shell structure, wherein the core includes a first polymer formed by a first encapsulating agent and denitrifying sludge encapsulated by the first polymer, and the shell includes a second polymer formed by a second encapsulating agent and nitrifying sludge encapsulated by the second polymer.
[0025] The present invention also provides the application of the double-layer gel granular sludge described in the above technical solution in the field of denitrification.
[0026] The present invention improves the cross-linking density and strength of the shell layer through the third cross-linking reaction, reduces the swelling phenomenon of the double-layer gel granular sludge after denitrification, and improves the stability of the double-layer gel granular sludge; and constructs a dissolved oxygen concentration gradient of anaerobic core layer and aerobic shell layer according to the limited oxygen transfer, so that the core layer of the double-layer gel granular sludge undergoes denitrification and the shell layer undergoes nitrification to achieve simultaneous nitrification and denitrification.
[0027] Furthermore, the preparation method of the present invention shortens the preparation time. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a process flow chart of an embodiment;
[0029] Figure 2 The actual pictures of the core-shell structure gel granular sludge in Example 1 before and after use;
[0030] Figure 3 The change of particle size of the core-shell structure gel granular sludge during use in Example 1;
[0031] Figure 4To control the denitrification effect of the core-shell gel granular sludge in Example 1 under the condition of controlling the dissolved oxygen at 4-6 mg / L;
[0032] Figure 5 To control the dissolved oxygen concentration gradient change law from the surface to the center point of the core-shell structure gel granular sludge in Example 1 under the condition of 4-6 mg / L dissolved oxygen. DETAILED DESCRIPTION
[0033] The present invention provides a method for preparing double-layer gel granular sludge, comprising the following steps:
[0034] (1) mixing a first embedding agent solution with denitrification sludge, and then mixing the obtained core layer embedding material with a first cross-linking agent solution to perform a first cross-linking reaction to obtain core layer gel granular sludge;
[0035] (2) mixing the second embedding agent solution with the nitrified sludge to obtain a shell embedding material;
[0036] (3) coating the core layer gel particle sludge with the shell layer embedding material, and then freezing the obtained coating to obtain double-layer frozen particles;
[0037] (4) mixing the double-layer frozen particles with a second cross-linking agent solution to perform a second cross-linking reaction, and then mixing the particles obtained by the second cross-linking reaction with a third cross-linking agent solution to perform a third cross-linking reaction to obtain the double-layer gel particle sludge;
[0038] There is no order of precedence for step (1) and step (2).
[0039] The invention mixes the first embedding agent solution with the denitrification sludge, and then mixes the obtained core layer embedding material with the first cross-linking agent solution to carry out the first cross-linking reaction to obtain the core layer gel granular sludge.
[0040] In the present invention, the first embedding agent solution preferably includes 8-12% polyvinyl alcohol by mass fraction. In a specific embodiment, the mass fraction of polyvinyl alcohol in the first embedding agent solution can be 8%, 9%, 10%, 11% or 12%.
[0041] In terms of mass fraction, the first embedding agent solution preferably includes 0.8-2% sodium alginate. In a specific embodiment, the mass fraction of sodium alginate in the first embedding agent solution may be 0.8%, 1%, 1.5% or 2%;
[0042] Calculated by mass fraction, the first embedding agent solution preferably includes a balance of water.
[0043] In the present invention, the method for preparing the first embedding agent solution preferably comprises the following steps:
[0044] Polyvinyl alcohol, sodium alginate and water are mixed, and then the resulting solution is cooled to room temperature to obtain the first embedding agent solution; the mixing temperature is preferably 85-95°C, and in a specific embodiment, the mixing temperature can be 85°C, 90°C or 95°C.
[0045] In the present invention, the suspended solids concentration of the denitrification sludge is 3 to 7 g / L, and the volatile suspended solids concentration is 2 to 5 g / L;
[0046] In the present invention, the method for preparing denitrification sludge preferably comprises the following steps: centrifuging the denitrification sludge raw material.
[0047] In the present invention, the temperature during centrifugation is preferably 4° C., and the rotation speed is preferably 5000 r / min.
[0048] In the present invention, the volatile suspended solids concentration of the denitrification sludge after centrifugation is 18-20 g / L.
[0049] In the present invention, the mass ratio of the first embedding agent solution to the denitrification sludge is preferably 1-3:1. In a specific embodiment, the mass ratio of the first embedding agent solution to the denitrification sludge can be 1:1, 1:1.5, 1:2, 1:2.5 or 1:3.
[0050] In the present invention, the method for preparing the first cross-linking agent solution preferably comprises the following steps:
[0051] The pH value of the saturated boric acid solution containing calcium chloride is adjusted to 5.7-6.3 with alkali solution.
[0052] In the present invention, the mass content of calcium chloride in the saturated boric acid solution containing calcium chloride is preferably 1-4%. In a specific embodiment, the mass content of calcium chloride in the saturated boric acid solution containing calcium chloride can be 1%, 2%, 3% or 4%.
[0053] In the present invention, the alkali solution preferably comprises a sodium hydroxide solution with a concentration of 1M.
[0054] In the present invention, mixing the obtained nuclear layer embedding material with the first cross-linking agent solution preferably comprises: dropping the nuclear layer embedding material into the first cross-linking agent solution.
[0055] In the present invention, the temperature of the first cross-linking reaction is preferably 4-30°C. In a specific embodiment, the temperature of the first cross-linking reaction can be 4°C, 10°C, 15°C, 20°C, 25°C or 30°C; the time is preferably 6-24h. In a specific embodiment, the time of the first cross-linking reaction can be 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.
[0056] In the first cross-linking reaction, the sodium ions on the sodium alginate molecular chain undergo an ion exchange reaction with calcium ions in a calcium chloride solution. The calcium ions replace the sodium ions and act as a "bridge" to connect different sodium alginate molecular chains to form a three-dimensional network structure gel; boric acid dissociates into borate ions in water, which react with the hydroxyl groups on the polyvinyl alcohol molecular chains to form borate ester bonds, making the polyvinyl alcohol molecular chains interconnected and cross-linked, thereby enhancing the stability of the gel system, synergizing with the sodium alginate gel, and improving the performance of the gel beads.
[0057] After the first cross-linking reaction, the present invention preferably further comprises: performing solid-liquid separation on the obtained first cross-linking reaction product, then washing the obtained solid, and then immersing the washed solid in a first cross-linking agent solution to obtain a mixture; performing solid-liquid separation on the mixture, removing moisture from the surface of the obtained wet solid, and obtaining the core layer gel granular sludge.
[0058] In the present invention, the immersion temperature is preferably 18-30°C. In a specific embodiment, the immersion temperature may be 18°C, 20°C, 25°C or 30°C. The immersion time is preferably 1-5 min. In a specific embodiment, the immersion time may be 1 min, 2 min, 3 min, 4 min or 5 min.
[0059] In the present invention, the particle size of the core layer gel granular sludge is preferably 2.5-3.5 mm. In a specific embodiment, the particle size of the core layer gel granular sludge can be 2.5 mm, 3.0 mm or 3.5 mm.
[0060] The present invention mixes the second embedding agent solution with the nitrified sludge to obtain the shell embedding material.
[0061] In the present invention, the second embedding agent solution preferably includes 8-12% polyvinyl alcohol by mass fraction. In a specific embodiment, the mass fraction of polyvinyl alcohol in the second embedding agent solution can be 8%, 9%, 10%, 11% or 12%.
[0062] In terms of mass fraction, the second embedding agent solution preferably includes 0.8-2% sodium alginate. In a specific embodiment, the mass fraction of sodium alginate in the second embedding agent solution may be 0.8%, 1%, 1.5%, or 2%;
[0063] Calculated by mass fraction, the second embedding agent solution preferably includes a balance of water.
[0064] In the present invention, the method for preparing the second embedding agent solution preferably comprises the following steps:
[0065] Polyvinyl alcohol, sodium alginate and water are mixed, and then the resulting solution is cooled to room temperature to obtain the second embedding agent solution; the mixing temperature is preferably 85-95°C, and in a specific embodiment, the mixing temperature can be 85°C, 90°C or 95°C.
[0066] In the present invention, the suspended solids concentration of the nitrification sludge is preferably 3 to 7 g / L, and the volatile suspended solids concentration is 2 to 5 g / L;
[0067] In the present invention, the method for preparing nitrification sludge preferably comprises the following steps: centrifuging the denitrification sludge raw material.
[0068] In the present invention, the temperature during centrifugation is preferably 4° C., and the rotation speed is preferably 5000 r / min.
[0069] In the present invention, the volatile suspended solids concentration of the centrifuged nitrification sludge is preferably 18 to 22 g / L.
[0070] In the present invention, the mass ratio of the second embedding agent solution to the nitrification sludge is preferably 1 to 3:1. In a specific embodiment, the mass ratio of the second embedding agent solution to the nitrification sludge can be 1:1, 1:1.5, 1:2, 1:2.5 or 1:3.
[0071] After obtaining the core layer gel granule sludge and the shell layer embedding material, the present invention uses the shell layer embedding material to coat the core layer gel granule sludge, and then freezes the obtained coating to obtain double-layer frozen particles.
[0072] In the present invention, the coating preferably includes the following steps: dripping the shell layer embedding material into half of the mold cavity, then putting the core layer gel particle sludge, and then continuing to drip the shell layer embedding material until the entire mold cavity is filled.
[0073] In the present invention, the mold preferably comprises a 36-hole circular silicone mold with a diameter of 8 mm.
[0074] In the present invention, the freezing temperature is preferably -20°C, and the freezing time is preferably 20 to 60 minutes. In a specific embodiment, the freezing time can be 20 minutes, 30 minutes, 40 minutes, 50 minutes or 60 minutes. Under the freezing condition, the PVA molecules are physically cross-linked to form microcrystals.
[0075] After obtaining the double-layer frozen particles, the present invention mixes the double-layer frozen particles with a second cross-linking agent solution to perform a second cross-linking reaction, and then mixes the particles obtained by the second cross-linking reaction with a third cross-linking agent solution to perform a third cross-linking reaction to obtain the double-layer gel particle sludge.
[0076] The present invention has no particular limitation on the amount of the second crosslinking agent solution and the third crosslinking agent solution, and the particles can be soaked in the solution.
[0077] In the present invention, the second cross-linking agent is preferably a saturated boric acid solution containing calcium chloride; the mass content of calcium chloride in the saturated boric acid solution containing calcium chloride is preferably 1-4%. In a specific embodiment, the mass content of calcium chloride in the saturated boric acid solution containing calcium chloride can be 1%, 2%, 3% or 4%.
[0078] In the present invention, the temperature of the second cross-linking reaction is preferably 18-30°C. In a specific embodiment, the temperature of the second cross-linking reaction may be 18°C, 20°C, 25°C or 30°C. The time is preferably 1-3h. In a specific embodiment, the time of the second cross-linking reaction may be 1h, 1.5h, 2h, 2.5h or 3h.
[0079] The second cross-linking reaction is a reaction of the frozen particles with a second cross-linking agent.
[0080] In the present invention, after the second cross-linking reaction, the method preferably further comprises: separating the second cross-linking reaction product into solid and liquid and washing the obtained solid with deionized water to obtain particles obtained by the second cross-linking reaction.
[0081] In the present invention, the third cross-linking agent solution includes one of a sodium sulfate solution, a potassium dihydrogen phosphate solution and a sodium nitrate solution; the concentration of the third cross-linking agent solution is preferably 0.5 to 3 M; in a specific embodiment, the concentration of the third cross-linking agent solution can be 0.5 M, 1 M, 1.5 M, 2 M, 2.5 M or 3 M.
[0082] In the present invention, the temperature of the third cross-linking reaction is preferably 18-30°C. In a specific embodiment, the temperature of the third cross-linking reaction can be 18°C, 20°C, 25°C or 30°C; the time is preferably 1-3h. In a specific embodiment, the time of the third cross-linking reaction can be 1h, 1.5h, 2h, 2.5h or 3h.
[0083] The third cross-linking reaction is the cross-linking and curing of the gel particles obtained by the second cross-linking with the third cross-linking agent: taking sodium sulfate as an example, sulfate ions penetrate into the gel beads and destroy the hydrogen bonds between PVA hydroxyl groups and water molecules by polarizing water molecules, promoting the formation of hydrogen bonds between PVA hydroxyl groups, and then forming PVA microcrystals. In addition, the PVA-SA gel beads cross-linked with sodium sulfate are less toxic to bacteria than boric acid, have higher stability in water, and have higher biological activity than traditional PVA-boric acid hydrogel beads.
[0084] After the third cross-linking reaction, the present invention preferably performs solid-liquid separation on the third cross-linking reaction product, and then washes the obtained solid to obtain the double-layer gel granular sludge.
[0085] In the present invention, the particle size of the double-layer gel granular sludge is preferably 7 to 8 mm.
[0086] The present invention also provides a double-layer gel granular sludge prepared by the preparation method described in the above technical scheme, which has a core-shell structure, wherein the core includes a first polymer formed by a first embedding agent and denitrification sludge in the first polymer, and the shell includes a second polymer formed by a second embedding agent and nitrification sludge in the second polymer.
[0087] The present invention also provides the application of the double-layer gel granular sludge described in the above technical solution in the field of denitrification.
[0088] The double-layer gel granular sludge provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0089] The process flow chart for preparing double-layer gel granular sludge in the embodiment is as follows Figure 1 As shown: polyvinyl alcohol (PVA), sodium alginate (SA) and concentrated denitrification sludge are mixed, and then dripped into a boric acid solution containing 2wt% calcium chloride and the pH value is adjusted to 5.7-6.3 by a 1M sodium hydroxide solution through a syringe to obtain core layer gel granular sludge; then PVA, SA and concentrated nitrification sludge are mixed and the core layer gel granular sludge is coated and frozen. After freezing, the obtained particles are placed in a saturated boric acid solution containing 2wt% calcium chloride and a 0.5M sodium sulfate solution for cross-linking to obtain core-shell structured gel granular sludge.
[0090] Example 1
[0091] Preparation of core gel granular sludge:
[0092] Dissolving polyvinyl alcohol, sodium alginate and water at 90° C. to obtain an embedding agent, and cooling to room temperature to obtain an embedding agent solution (the mass fraction of polyvinyl alcohol is 12%, the mass fraction of sodium alginate is 1% and the balance is water);
[0093] Denitrification sludge from the anaerobic zone of Qilidian Wastewater Treatment Plant in Guilin, Guangxi Zhuang Autonomous Region, China was placed in a closed SBR reactor and then simulated domestic sewage [nitrate nitrogen 25 mg N / L, sodium bicarbonate 600 mg / L, sodium acetate 400 mg COD / L, phosphate 5 mg P / L, MgSO4·7H2O (48.5 mg / L), CaCl2·2H2O (10 mg / L), 1 mL / L trace elements [FeCl2·7H2O (6.985 g / L), MnCl2·4H2O (0.099 g / L), ZnSO4·7H2O (0.144 g / L), CuCl2 (0.017 g / L), CoCl2·6H2O (0.0238 g / L), NiCl2·6H2O (0.034 g / L)] was added. (0.0238 g / L), Na2MoO4·2H2O(0.036 g / L)], acclimated under anaerobic conditions (DO<0.2 mg / L) until the effluent was stable and the denitrification rate reached 95%, then the acclimated denitrification sludge was centrifuged and concentrated at 5000 rpm and 4°C, the volatile suspended solids concentration of the concentrated denitrification sludge was 19.2 g / L, the embedding agent solution was mixed with the concentrated denitrification sludge at a mass ratio of 1:1 to obtain denitrification gel sludge;
[0094] Weigh boric acid and calcium chloride dihydrate powder, add water to dissolve, and prepare a saturated boric acid solution containing 2 wt% calcium chloride. Then adjust the pH to 5.7-6.3 with a 1 M sodium hydroxide solution to obtain a first crosslinking agent solution;
[0095] The denitrification gel sludge was dropped into the first cross-linking agent solution through a syringe, and filtered after solidification at 4°C for 12 hours. The filtered solid was then washed with deionized water and immersed in the first cross-linking agent solution for 2 minutes. The surface moisture was wiped off to obtain the core layer gel granular sludge.
[0096] Preparation of core-shell structured gel granular sludge:
[0097] Dissolve polyvinyl alcohol and sodium alginate at 90°C to obtain an embedding agent, and after cooling to room temperature, obtain an embedding agent solution (the mass fraction of polyvinyl alcohol is 12%, the mass fraction of sodium alginate is 1% and the balance is water);
[0098] Nitrified sludge from the aerobic zone of Qilidian Wastewater Treatment Plant in Guilin, Guangxi Zhuang Autonomous Region, China was placed in an open SBR reactor and then added with simulated domestic sewage [nitrate nitrogen 25 mgN / L, sodium bicarbonate 600 mg / L, sodium acetate 400 mg COD / L, phosphate 5 mg P / L, MgSO4·7H2O (48.5mg / L), CaCl2·2H2O (10mg / L), 1mL / L trace elements (FeCl2·7H2O (6.985g / L), MnCl2·4H2O (0.099g / L), ZnSO4·7H2O (0.144g / L), CuCl2 (0.017g / L), CoCl2·6H2O (0.0238g / L), NiCl2·6H2O (0.0238g / L), Na2MoO4·2H2O (0.036g / L)], and intermittent aeration (DO) was performed by an aeration device. 4-6mg / L), acclimatize until the effluent is stable and the denitrification rate reaches 95%, then centrifuge and concentrate the nitrified sludge after acclimatization at 5000rpm and 4°C, and the volatile suspended solids concentration of the concentrated nitrified sludge is 21.2g / L;
[0099] The embedding agent solution and the concentrated nitrified sludge are mixed in a mass ratio of 1:1 to obtain nitrified gel sludge;
[0100] Weigh boric acid and calcium chloride dihydrate powder, add water to dissolve, and prepare a saturated boric acid solution containing 2 wt % calcium chloride to obtain a second cross-linking agent solution;
[0101] A 0.5 M Na2SO4 solution was prepared as the third cross-linking agent solution.
[0102] Use a syringe to drop the nitrogel sludge into a 36-hole circular silicone mold with a pore size of 8 mm to half the volume of the mold cavity, then put in the core layer gel granular sludge, and then drop the nitrogel sludge to wrap the core layer gel granular sludge, and then freeze it at -20°C for 40 minutes to form a core-shell structure gel, and then put the core-shell structure gel into 200mL of the second cross-linking agent solution for cross-linking and curing at 25°C for 2h. After solid-liquid separation, put it in 200mL of the third cross-linking agent solution at 25°C for further curing for 2h. After solid-liquid separation, wash it with deionized water and store it in a 4°C refrigerator to obtain a core-shell structure double-layer gel granular sludge.
[0103] Denitrification experiment
[0104] Simulated domestic sewage was prepared with the following components: ammonia nitrogen 25 mgN / L, sodium bicarbonate 600 mg / L, sodium acetate 400 mgCOD / L, phosphate 5 mg P / L, MgSO4·7H2O (48.5 mg / L), CaCl2·2H2O (10 mg / L), 1 mL / L trace elements (FeCl2·7H2O (6.985 g / L), MnCl2·4H2O (0.099 g / L), ZnSO4·7H2O (0.144 g / L), CuCl2 (0.017 g / L), CoCl2·6H2O (0.0238 g / L), NiCl2·6H2O (0.0238 g / L), Na2MoO4·2H2O (0.036 g / L)).
[0105] Double-layer gel granular sludge with core-shell structure was added to simulated domestic sewage (volume ratio of sewage to sludge was 30:1). An air flow meter was used to adjust the aeration flow rate and control the dissolved oxygen at 4-6 mg / L. The simulated sewage was replaced every two days for a total of 20 days. 10 mL of water samples were taken at 0, 6, 12, 24, 36, and 48 hours in each cycle, and filtered with a 0.22 μm filter after centrifugation to monitor the removal of ammonia nitrogen and total nitrogen.
[0106] Figure 2 The actual pictures of the core-shell structure gel granular sludge in Example 1 before and after use are shown in FIG. Figure 3 The change of particle size of the core-shell structure gel granular sludge during use in Example 1;
[0107] Depend on Figures 2-3 It can be seen that the average particle size of the prepared core-shell structure gel granular sludge is 7.2 mm, and the average particle size after the denitrification experiment is 7.5 mm. Compared with the gel granular sludge before the experiment, it has expanded by 4.2%, the expansion rate is small, and there is no breakage, and the stability performance is good.
[0108] Figure 4 To control the dissolved oxygen at 4-6 mg / L, the denitrification effect of the core-shell structure gel granular sludge of Example 1 was used.
[0109] Depend on Figure 4 It can be seen that the effluent ammonia nitrogen concentration is 0-0.5 mg / L, the effluent total nitrogen concentration is 0.6-6.1 mg / L, the gel granular sludge has a removal rate of 97.7-99.8% for ammonia nitrogen and 75.9-97.5% for total nitrogen, which meets the Class A standard in the Pollutant Discharge Standard for Urban Wastewater Treatment Plants (GB 18918-2002).
[0110] The penetration depth of dissolved oxygen in the double-layer gel granular sludge after the denitrification experiment was tested using an oxygen microelectrode:
[0111] Saturated sodium sulfite solution was prepared as an oxygen-free solution, and air was passed through deionized water for 10 minutes as an oxygen-saturated solution to perform linear calibration on the oxygen microelectrode. In simulated domestic sewage, the gel granular sludge was fixed in a silicone mold with a syringe needle, and the tip of a stainless steel oxygen needle electrode (OX-N, Unisense, Denmark) with a tip diameter of 1 mm was positioned on the surface of the granular sludge by a motor-driven micromanipulator (MMS-903992, Unisense, Denmark). The step size was set to 200 μm to test the dissolved oxygen concentration at different depths of the granular sludge, and the dissolved oxygen curve was recorded by software (SensorTrace, version 3.4.300, Unisense, Denmark).
[0112] Figure 5 This is the variation law of dissolved oxygen concentration gradient from the surface to the center point of the core-shell structure gel granular sludge in Example 1 under the condition of dissolved oxygen of 4-6 mg / L.
[0113] Depend on Figure 5 It can be seen that when the dissolved oxygen concentration drops from 5.8 mg / L on the surface to 0.5 mg / L, the depth of the microelectrode test is 2.3 mm, and this area is the aerobic zone; when the dissolved oxygen concentration continues to drop to 0.2 mg / L, the depth reaches 2.4 mm, and this area is the anoxic zone; the area from 2.4 mm to the center of the granular sludge is the anaerobic zone. The core-shell double-layer gel granular sludge has an obvious dissolved oxygen concentration gradient, forming a microenvironment of aerobic, anoxic, and anaerobic zones, which can achieve simultaneous nitrification, denitrification, and denitrification treatment.
[0114] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing double-layer gel granular sludge, characterized in that: The following steps are involved: (1) mixing a first embedding agent solution with denitrification sludge, and then mixing the obtained core layer embedding material with a first cross-linking agent solution to perform a first cross-linking reaction to obtain core layer gel granular sludge; (2) mixing the second embedding agent solution with the nitrified sludge to obtain a shell embedding material; (3) coating the core layer gel particle sludge with the shell layer embedding material, and then freezing the obtained coating to obtain double-layer frozen particles; (4) mixing the double-layer frozen particles with a second cross-linking agent solution to perform a second cross-linking reaction, and then mixing the particles obtained by the second cross-linking reaction with a third cross-linking agent solution to perform a third cross-linking reaction to obtain the double-layer gel particle sludge; There is no order of precedence for step (1) and step (2).
2. The preparation method according to claim 1, characterized in that: Calculated by mass fraction, the first embedding agent solution and the second embedding agent solution independently include 8-12% polyvinyl alcohol, 0.8-2% sodium alginate and the balance water.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the first embedding agent solution to the denitrification sludge is 1 to 3:1; The mass ratio of the second embedding agent solution to the nitrified sludge is 1 to 3:
1.
4. The preparation method according to claim 1, characterized in that: The method for preparing the first cross-linking agent solution comprises the following steps: Adjust the pH value of the saturated boric acid solution containing calcium chloride to 5.7-6.3 with alkali solution; The mass content of calcium chloride in the saturated boric acid solution containing calcium chloride is 1-4%.
5. The preparation method according to claim 1, characterized in that: The temperature of the first cross-linking reaction is 4 to 30° C., and the time is 6 to 24 hours.
6. The preparation method according to claim 1, characterized in that: After the first cross-linking reaction, the method further includes: performing solid-liquid separation on the obtained first cross-linking reaction product, then washing the obtained solid, and then immersing the washed solid in a first cross-linking agent solution to obtain a mixture; performing solid-liquid separation on the mixture, removing moisture from the surface of the obtained wet solid, and obtaining the core layer gel granular sludge.
7. The preparation method according to claim 1, characterized in that: The second cross-linking agent is a saturated boric acid solution containing calcium chloride; the mass content of calcium chloride in the saturated boric acid solution containing calcium chloride is 1 to 4%; The second cross-linking reaction time is 1 to 3 hours.
8. The preparation method according to claim 1, characterized in that: The third cross-linking agent solution includes one of a sodium sulfate solution, a potassium dihydrogen phosphate solution and a sodium nitrate solution; the concentration of the third cross-linking agent solution is 0.5 to 3M; and the time of the third cross-linking reaction is 1 to 3 hours.
9. The double-layer gel granular sludge prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The invention has a core-shell structure, wherein the core comprises a first polymer formed by a first embedding agent and denitrification sludge embedded by the first polymer, and the shell comprises a second polymer formed by a second embedding agent and nitrification sludge embedded by the second polymer.
10. Application of the double-layer gel granular sludge according to claim 9 in the field of denitrification.
Citation Information
Patent Citations
Preparation of SRB (sulfate reducing bacterium) biological inhibitor and method for inhibiting SRB in crude oil
CN103114085A
Double-loaded core-shell hydrogel, preparation method and application thereof
CN109734174A
Nitration embedded particle for sewage treatment and preparation method thereof
CN115432811A
Microcapsule encapsulating denitrifying bacteria and production method thereof
JP2011078911A